Fenomena dan Perilaku Belanja Online Melalui Tiktok Shop pada Generasi Z Perspektif Konsumsi Islam - majid, khikam ali; Rahmawati, Lilik (Jurnal Ilmiah Ekonomi Islam, 2024)
Abstract Online shopping through TikTok Shop has become a significant phenomenon among Generation Z, transforming the modern trading landscape. In this context, it is important to understand how this phenomenon affects the consumption behavior of Generation Z from an Islamic perspective. This study uses a qualitative approach with in-depth interviews and content analysis to investigate the phenomenon and online shopping behavior through TikTok Shop from the perspective of Islamic consumption. The research findings indicate that online shopping through TikTok Shop significantly influences the consumption behavior of Generation Z in the context of Islamic consumption. They tend to choose products that align with Islamic values, such as halal and environmentally friendly products. The content presented on TikTok Shop also affects consumer shopping patterns, both positively and negatively, depending on its alignment with Islamic teachings. However, there are also challenges faced by Generation Z consumers in ensuring compliance with Islamic consumption principles when shopping online through TikTok Shop. One of these challenges is uncertainty about the halal status of the products offered and the influence of content that does not always align with Islamic values. Therefore, further efforts are needed from various parties to increase consumer awareness and provide products and content that better align with Islamic consumption principles.This research provides valuable insights into how the phenomenon of online shopping through TikTok Shop influences the consumption behavior of Generation Z from an Islamic perspective. The implications of this research can be used as a basis for developing better policies to support sustainable consumption and adherence to Islamic principles in the rapidly evolving digital trading era. Keywords : Phenomenon, Online Shopping through, Tiktok Shop, Generation Z, Islamic Consumption. Abstrak Belanja online melalui TikTok Shop telah menjadi fenomena signifikan di kalangan Generasi Z, mengubah lanskap perdagangan modern. Dalam konteks ini, penting untuk memahami bagaimana fenomena ini memengaruhi perilaku konsumsi Generasi Z dari sudut pandang Islam. Studi ini menggunakan pendekatan kualitatif dengan wawancara mendalam dan analisis konten untuk menyelidiki fenomena dan perilaku belanja online melalui TikTok Shop dari perspektif konsumsi Islam. Temuan penelitian menunjukkan bahwa belanja online melalui TikTok Shop secara signifikan memengaruhi perilaku konsumsi Generasi Z dalam konteks konsumsi Islam. Mereka cenderung memilih produk yang sejalan dengan nilai-nilai Islam, seperti produk halal dan ramah lingkungan. Konten yang disajikan di TikTok Shop juga memengaruhi pola belanja konsumen, baik secara positif maupun negatif, tergantung pada kesesuaiannya dengan ajaran Islam. Namun, ada juga tantangan yang dihadapi konsumen Generasi Z dalam memastikan kepatuhan dengan prinsip konsumsi Islam saat berbelanja online melalui TikTok Shop. Salah satu tantangan ini adalah ketidakpastian tentang status halal produk yang ditawarkan dan pengaruh konten yang tidak selalu sejalan dengan nilai-nilai Islam. Oleh karena itu, upaya lebih lanjut diperlukan dari berbagai pihak untuk meningkatkan kesadaran konsumen dan menyediakan produk dan konten yang lebih sejalan dengan prinsip konsumsi Islam. Penelitian ini memberikan wawasan berharga tentang bagaimana fenomena belanja online melalui TikTok Shop memengaruhi perilaku konsumsi Generasi Z dari sudut pandang Islam. Implikasi dari penelitian ini dapat digunakan sebagai dasar untuk mengembangkan kebijakan yang lebih baik untuk mendukung konsumsi yang berkelanjutan dan kepatuhan terhadap prinsip Islam dalam era perdagangan digital yang berkembang pesat. Kata Kunci: Fenomena, Perilaku Belanja Online, Toko Tiktok, Generasi Z, Konsumsi Islam. Abstract Online shopping through TikTok Shop has become a significant phenomenon among Generation Z, transforming the modern trading landscape. In this context, it is important to understand how this phenomenon affects the consumption behavior of Generation Z from an Islamic perspective. This study uses a qualitative approach with in-depth interviews and content analysis to investigate the phenomenon and online shopping behavior through TikTok Shop from the perspective of Islamic consumption. The research findings indicate that online shopping through TikTok Shop significantly influences the consumption behavior of Generation Z in the context of Islamic consumption. They tend to choose products that align with Islamic values, such as halal and environmentally friendly products. The content presented on TikTok Shop also affects consumer shopping patterns, both positively and negatively, depending on its alignment with Islamic teachings. However, there are also challenges faced by Generation Z consumers in ensuring compliance with Islamic consumption principles when shopping online through TikTok Shop. One of these challenges is uncertainty about the halal status of the products offered and the influence of content that does not always align with Islamic values. Therefore, further efforts are needed from various parties to increase consumer awareness and provide products and content that better align with Islamic consumption principles.This research provides valuable insights into how the phenomenon of online shopping through TikTok Shop influences the consumption behavior of Generation Z from an Islamic perspective. The implications of this research can be used as a basis for developing better policies to support sustainable consumption and adherence to Islamic principles in the rapidly evolving digital trading era. Keywords : Phenomenon, Online Shopping through, Tiktok Shop, Generation Z, Islamic Consumption.